(3GdJMQjQ aj abg GdRjOjIs - (3CHh WGdH jMji Hf GdMSjf Hf GdbGSe Hf gGQhf Hf CHj YjSi Hf Ydj GdgGQhfj,J (B424 (3g` s ((3CMeO Hf ehSi Hf eMeO Hf CMeO GdMLhQi GdCSdei s)
(3ChdgG (B:s
(3GdMeO ddg Ydi LRjd fYeJg , hSfi ehgHJg SCdJ habc Gddg hEjGfG dWGYJg , hJdNjU ePGgH GdbGSe Hf EHQGgje hjMi Hf GdMSjf hChdGOgeG s
(3BNQgG (B:s
(3aEf CSde Ndi SHjdg , hEf CHj bJd hdG jSJQb , hEf cGf cGaQkG ai GdCUd hdMb HOGQ GdMQH Ydi caQg ESJQb Je cJGH s
(3cJHJ HYV GdYfhGfGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B141s
(3JHUQGJ GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis